The Differences in Patient Safety Culture (Before and After Training) over Patient Safety on Pharmacy and Radiological Installations at Type B Hospital, Jakarta - Desy Trisnawati; Rokiah Kusumapradja; Idrus Jus’at (Journal of Multidisciplinary Academic, 2020)
Based on 20% incidents are associated with pharmaceutical and radiological installations. A quasi experiment design with pre-test and post-test without control was employed. There were 43 health personals was involved in this study: 33 from pharmaceutical and 10 from radiology installations without randomization. This study aimed to evaluate the effectiveness of training on patients’ safety culture among pharmaceutical and radiology personal’s installations at a type B hospital in Jakarta. The Hospital Survey of Patient Safety Culture (HSOPSC) developed by Agency for Health Care Research and Quality (AHRQ) questionnaire was applied in the data collection. To evaluate the impact of training, Wilcoxon Sign Rank test was employed. The data analysis technique used was the Wilcoxon Signed Rank Test, to assess the differences between the variables tested. The training was significantly improving the patient’s safety culture among those two installations’ personals (p < 0,05). There was an increase in 8 dimensions of patient safety culture.